Stroke survivors' expectations and post-intervention perceptions of mindfulness training: A qualitative study. Issue 10 (26th November 2022) - Wrapson, Wendy; Dorrestein, Marlies; Wrapson, Jill; Theadom, Alice; Kayes, Nicola; Snell, Deborah; Rutherford, Sandy; Roche, Maree; Babbage, Duncan R.; Siegert, Richard J.
ABSTRACT: Depression and anxiety are common sequelae of stroke, occurring in at least one-third of patients. This study evaluated the acceptability and feasibility of providing mindfulness training (MT) to stroke survivors with the aim of reducing depression and anxiety. Following a six-week one-on-one MT course, 17 participants were interviewed. The median age of participants was 71, and 10 participants were male. This paper focuses on participants' expectations of the MT and their views about its impact on their everyday lives. Conventional content analysis was used for coding and analysis. A single theme, Seizing rehabilitation opportunities, was captured in relation to expectations of MT, and four themes provided information relating to participants' perceived impact of the course: Calming the mind, Reduced reactivity, Remedying physical symptoms, and Not quite there yet . Most participants knew little about mindfulness before the MT and did not have specific goals in mind when volunteering to take part. The findings suggest that most participants considered MT beneficial through reducing stress and giving them additional skills to cope with their everyday lives. A tailored mindfulness intervention may be a useful adjunct to other rehabilitation therapies for stroke survivors.